RESPON PESERTA DIDIK KELAS V SEKOLAH DASAR TERHADAP PENGEMBANGAN LKPD PENDIDIKAN KONSERVASI TOPIK FAUNA PADA MATA PELAJARAN IPAS - Apriliani, Dina; Andriana, Encep; Hendracipta, Nana (STKIP Persada Khatulistiwa Sintang, 2024)
Student Worksheets (LKPD) are an important aspect in implementing learning. This study aims to determine students' responses related to the development of LKPD in conservation education learning with the topic of fauna in Ujung Kulon National Park in the subject of science at grade V of elementary school. The study was conducted at SDN Kota Baru with the research subjects were 27 grade V students. The type of research used is descriptive research. Based on the results of the student response questionnaire on the aspect of interest, the percentage score was 93%, the percentage of the material aspect was 91%, the percentage of the linguistic aspect was 90% and the aspect of benefits was 94%. Therefore, the average percentage score was 92% with the category